24-hour simultaneous mPFC’s miniature 2-photon imaging, EEG-EMG, and video recording during natural behaviors - Jiaying Han; Fangxu Zhou; Zhong Zhao; Dong Zhang; Xueli Chen; Li Wang; Ting Zhao; Wei Ye; Xiaochun Gu; Huaqiang Fang; Jue Zhang; Lifeng Zhang; et al. (Scientific Data)
Abstract The medial prefrontal cortex (mPFC) coordinates cognitive processes across multiple timescales, yet its role in multiple natural behaviors remain unclear. Existing neural recording methods are limited by short observation windows and artificial task constraints, preventing insights into extended, naturally relevant dynamics. Here, we present multimodal datasets integrating two-photon calcium imaging via miniature microscope, simultaneous behavior video recording, and continuous EEG-EMG recordings in freely moving mice for over 24 hours. These datasets capture uninterrupted neural activity (unconstrained calcium imaging), physiological rhythms, and naturalistic behaviors (12 classified states) across full circadian cycles. By bridging three critical gaps: long-term continuity (over 24 hours of recording), multiple spontaneous behavior (unrestrained freely moving mice), and multimodal integration (neural activity, brain states, and behavior), our work establishes an open-access benchmark for naturalistic neuroscience. These data enable investigations into how mPFC ensembles dynamically reconfigure across timescales, advancing computational models of cortical dynamics and offering new insights into experience-dependent plasticity and cross-modal interactions in real-world contexts.